Anxiety symptoms, cerebral amyloid burden and memory decline in healthy older adults without dementia: 3-year prospective cohort study. (May 2014) - Pietrzak, Robert H.; Scott, J. Cobb; Neumeister, Alexander; Lim, Yen Ying; Ames, David; Ellis, Kathryn A.; Harrington, Karra; Lautenschlager, Nicola T.; Szoeke, Cassandra; Martins, Ralph N.; Masters, Colin L.; Villemagne, Victor L.; et al.
Summary: Although beta-amyloid, anxiety and depression have been linked cross-sectionally to reduced memory function in healthy older adults without dementia, prospective data evaluating these associations are lacking. Using data from an observational cohort study of 178 healthy older adults without dementia followed for 3 years, we found that anxiety symptoms significantly moderated the relationship between beta-amyloid level and decline in verbal (Cohen's d = 0.65) and episodic (Cohen's d = 0.38) memory. Anxiety symptoms were additionally linked to greater decline in executive function, irrespective of beta-amyloid and other risk factors. These findings suggest that interventions to mitigate anxiety symptoms may help delay memory decline in otherwise healthy older adults with elevated beta-amyloid.